2019
DOI: 10.1136/injuryprev-2018-043062
|View full text |Cite
|
Sign up to set email alerts
|

Identifying sociodemographic risk factors associated with residential fire fatalities: a matched case control study

Abstract: ObjectivesThis study aimed to investigate the association between sociodemographic factors and residential fire fatalities in Sweden. A majority of fatal fires occur in housing. An understanding of risk factors and risk groups is a must for well-founded decisions regarding targeted prevention efforts. There is a lack of consideration of the interrelation between sociodemographic factors and fire fatalities and there is a lack of high quality large-scale studies.MethodsIn this matched case-control study, reside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Existing literature has extensively discussed factors associated with residential fires and individuals characteristics, their socio-economic conditions, the built environment that they are living in and the fire circumstances. Individual characteristics such as age, gender, socio-economic status, occupants behaviour, poor mobility or alcohol intoxication ( Harpur et al, 2013 , Jonsson, 2017 , Jonsson et al, 2017 , Jonsson and Jaldell, 2020 , Nilson and Bonander, 2021 , Runefors and Nilson, 2021 , Tannous and Agho, 2017 , Turner et al, 2017 , Xiong et al, 2015 , Xiong et al, 2017 ) as well as the type of building ( Xiong et al, 2015 , Špatenková and Virrantaus, 2013 ), furniture ( Thomas et al, 2016 ), smoke alarm and fire safety measures ( Thomas and Bruck, 2010 , Istre et al, 2001 ) and fire circumstances such as electricity, cooking and smoking materials ( Xiong et al, 2015 , Ahrens, 2013 , Xiong et al, 2017 ) have been associated as risk and protective factors for deaths and injuries in residential fire incidents. Those younger than 5 years old or older than 65, being male, being unemployed and having lower educational attainment, alcohol and smoking and living in socioeconomically disadvantaged areas have been shown to increase the risk of experiencing residential fires and worsen health outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing literature has extensively discussed factors associated with residential fires and individuals characteristics, their socio-economic conditions, the built environment that they are living in and the fire circumstances. Individual characteristics such as age, gender, socio-economic status, occupants behaviour, poor mobility or alcohol intoxication ( Harpur et al, 2013 , Jonsson, 2017 , Jonsson et al, 2017 , Jonsson and Jaldell, 2020 , Nilson and Bonander, 2021 , Runefors and Nilson, 2021 , Tannous and Agho, 2017 , Turner et al, 2017 , Xiong et al, 2015 , Xiong et al, 2017 ) as well as the type of building ( Xiong et al, 2015 , Špatenková and Virrantaus, 2013 ), furniture ( Thomas et al, 2016 ), smoke alarm and fire safety measures ( Thomas and Bruck, 2010 , Istre et al, 2001 ) and fire circumstances such as electricity, cooking and smoking materials ( Xiong et al, 2015 , Ahrens, 2013 , Xiong et al, 2017 ) have been associated as risk and protective factors for deaths and injuries in residential fire incidents. Those younger than 5 years old or older than 65, being male, being unemployed and having lower educational attainment, alcohol and smoking and living in socioeconomically disadvantaged areas have been shown to increase the risk of experiencing residential fires and worsen health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, residential occupants alerted by a smoke alarm may not have the physical or cognitive capacity to evacuate safely. Previous literature has indicated that for a specific socio-economic subgroup of individuals, certain fire safety measures may be very useful and not so effective for the others and that the results regarding specific interventions may differ based on the group that receives it ( Jonsson and Jaldell, 2020 , Nilson and Bonander, 2021 , Runefors et al, 2016 ). Smoke alarms appear most effective in fires that are not initiated by children playing with fire ( Istre et al, 2002 ) and in properties in which, there are not any vulnerable residents present ( Marshall et al, 1998 ).…”
Section: Introductionmentioning
confidence: 99%
“…Whilst the reason for the varied results regarding certain interventions could be methodological or technical, it could also be that the effect differs depending upon the group that receives the intervention. Specifically, although safety interventions can be evaluated on a general, national or local level, it is widely known that fire mortality is distinctly affected by sociodemographic factors [14]. Returning to the five points in the fire process [5], it can be presumed that the overrepresentation of certain subgroups in term of the risk of fire mortality is due to sociodemographic factors affecting one or several of these points.…”
Section: Introductionmentioning
confidence: 99%
“…Of those who die in fires each year, *Correspondence should be addressed to: Johanna Gustavsson, E-mail: johanna.gustavsson@ kau.se approximately 75% die in their homes [2]. One group that appears to be particularly at risk is older people [3,4]. Given predictions of an aging society [5], it is reasonable to expect the number of fire fatalities to grow rather than decline in this group.…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, the Swedish Civil Contingencies Agency (MSB) issued a Vision Zero concerning fire deaths for Sweden [28]. This adoption has resulted in numerous initiatives to understand the question of who dies in fires in Sweden, and how these might be prevented [1][2][3][4][29][30][31][32]. Identification of the fact that most fire fatalities occur in homes, and that older people represent a particularly vulnerable risk group, lead MSB to issue public guidelines to the Municipal Fire and Rescue Services (FRS) concerning IFS in 2013 [33], introducing a concept for systematic fire safety targeting vulnerable groups, including criteria for identification of risk individuals and their needs to reduce fire risk.…”
Section: Introductionmentioning
confidence: 99%